Effectiveness of Hyperbaric Ropivacaine over Hyperbaric Bupivacaine in Spinal Anaesthesia - Ghimire, Ramesh (Europasian Journal of Medical Sciences, 2019)
Introduction: Spinal anesthesia is widely recognized as an alternative to general anesthesia for the surgery in lower extremities, perineum or lower body wall. The aim of the study was to compare the effectiveness and safety of hyperbaric Bupivacaine over hyperbaric Ropivacaine . Materials and Methods: We enrolled 60 patients of either sex, ASA grade I &II who were randomly allocated in two groups. Group-B received 3 ml of 0.5% hyperbaric Bupivacaine with glucose 8% and Group-R received 3ml of 0.5% hyperbaric Ropivacaine glucose 8.33%. The various parameters of the subarachnoid block, hemodynamic variables, recovery from sensory and motor blockade and side effects were studied. Result: The time to onset of maximum sensory block level was faster in Bupivacaine (9.10±3.90min) than in Ropivacaine (10.87±5.37min) and statistically not significant. The time to 5 segments regression was faster in Ropivacaine (116.00±29.72min) than Bupivacaine (143.50±18.76min) and the time to S2 level regression of sensory block was faster in Ropivacaine (154.00±27.84min) than Bupivacaine (186.00±18.73min). The time to onset of the maximum motor was faster with Bupivacaine (8.70±3.19min) as compared to Ropivacaine (13.10±4.40min) The time to regression of motor block by 1 grade was faster with Ropivacaine (97.00±26.64min) than Bupivacaine (146.50±23.53min) and the time to complete regression of motor block was faster with Ropivacaine (149.00±30.75min) than Bupivacaine (183.50±19.96min). Conclusion: The hyperbaric Ropivacaine (3ml, 0.5%) provides a reliable subarachnoid block of shorter duration than hyperbaric Bupivacaine (3ml, 0.5%) with stable hemodynamic parameters.